(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
To investigate of developing the creative writing instructional model (CWIM) to enhance writing on Thai language subject for creating learning qualities and achievements of students’ abilities toward their improving writing skills on Thai literature with a sample of 339 opportunity extension students at the ninth-grade level, 42 Thai teachers in the 8-Opportunity Extension Schools in Thailand. Students’ and teachers’ perceptions of their problems and needs to their creative thinking of the principal of CWIM, such as; purpose, syntax, social system, responding principal, and supporting system. The 10-lesson plans, the 36-items CWIM, and the 10-items Instructional Suitability Questionnaire were assessed. Statistically significant with the efficiency of the six thinking principal to set for developing the CWIM was 80.26/81.17, students’ and teachers’ needs of their problems are higher evidence level, students’ satisfaction on syntax activity processes of their learning achievements and abilities with lesson plans were achieved for creative writing skills, increasingly.